Measuring Efficiency and Productivity Change of Multi-Specialty Private Sector Hospitals in India : A DEA Based Malmquist Productivity Index Approach - Prathibha Patel, M.; Ranjith, V. K. (Indian Journal of Finance, 2018)
This study analyzed the efficiency of 28 un-listed standalone multi-speciality private sector hospitals in India with panel data from 2012-2013 to 2014-2015 using Malmquist data envelopment analysis. The study used number of beds, number of physicians, and number of other medical staff as input variables. Number of inpatients, number of outpatients, and number of major surgeries were used as output variables. While output oriented CCR and BCC models were used to estimate the technical and scale efficiencies, Malmquist productivity index was used to evaluate productivity changes over years in terms of technical efficiency change and technological change. The values by which inefficient hospitals should increase their outputs and/or decrease their inputs were estimated hospital wise across 3 years. The estimations presented current levels of different efficiency parameters and facilitated the overall evaluation of individual hospitals based on the values and their increase/decrease. It was found that the hospitals achieved a moderate productivity growth of 6.3% during the period of the study. The results of the study also provided critical implications for hospital managers.